Kyai's Leadership Style in Increasing Santri Interprenuer During the Covid-19 Pandemic: Gaya Kepemipinan Kiyai Dalam Peningkatan Interprenuer Santri Pada Masa Pandemi Covid-19 - wakit , Saipul; Nurdiana, Ilfi; Yuliana, Indah (Halaqa: Islamic Education Journal, 2022)
The impact of the COVID-19 pandemic certainly demands that everyone and educational institutions be creative and innovative and rise from adversity in the education, health and economic sectors. As for efforts to revive the economic sector during the pandemic and welcome the new normal, joint efforts are needed to generate both macro and micro economies such as UMKM, home industries and other creative economies in society. The solution that can be taken in overcoming the economic crisis from the impact of COVID-19 is to empower UMKM in the community and carry out interprenuership social movements. This is as has been done by Islamic boarding schools by carrying out several entrepreneurial activities to provide knowledge, skills, skills, mentality and instill a spirit of independence among students. This can go well, of course, cannot be separated from the role of the leader in it who motivates, moves, evaluates and makes strategic efforts. In this study using a qualitative method with a case study approach by extracting primary and secondary data with interviews, observation and documentation. Practically, the results of this research show that the role of the kyai in providing motivation is carried out in several varied methods according to the situation and conditions. As for how to move students, it is done by enabling leadership and structure, while the evaluation is carried out directly or indirectly with a practical approach. Practically, efforts to increase entrepreneurship are carried out through education, training, field studies, discussions, tutorials and expert lectures. Substantively in increasing entrepreneurship, the role of institutional leaders is needed in coordinating, mobilizing, motivating and evaluating with applicable examples.